Carnival and Class Structure: Participation Dynamics and Social Relations in the Recife and Olinda Carnival - Carri, Javier; Galle, Alberto Antonio Emilio (Millcayac - Revista Digital de Ciencias Sociales, 2025)
This article seeks to understand the carnival of Recife and Olinda as a complex cultural phenomenon shaped by class struggles, identity tensions, and institutional control practices. Within the context of carnival celebrations, it explores how cultural participation practices express, reinforce, or challenge the structure of social classes and power relations. A qualitative research strategy was employed, combining three methodological tools: participant observation, open-ended interviews, and textual analysis. The findings indicate that the carnival not only reproduces social hierarchies and mechanisms of state control, but also simultaneously functions as a space for resistance and cultural transformation, where participants actively negotiate, contest, and reinterpret power relations. Moreover, public cultural policies exhibit a dual character: they expand participation while concurrently perpetuating structural inequalities. Collectively, the study underscores the complex interplay between power structures and popular resistance and creativity, positioning the carnival as a dynamic arena of social tension and transformation.